1982
DOI: 10.1007/bf00303003
|View full text |Cite
|
Sign up to set email alerts
|

Pairing of X and Y chromosomes, non-inactivation of X-linked genes, and the maleness factor

Abstract: In this paper observations are summarized and speculations discussed, and it is suggested that some loci on the distal short arm of the X chromosome (Xp) are not randomly inactivated in the female, because they are within the proximal part of the pairing segment between Xp and Yp. This peculiarity of gene expression may be a remnant of the evolutionary history of the sex chromosomes, the pairing segment of which may involve at least 27% of Xp and 95% of Yp. Crossing over seems to occur mostly in the terminal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…This segment is of considerable interest because in this region, a reduction of X inactivation has been observed (Mohandas et al 1979;Miiller et al 1980;Migeon et al 1982). Furthermore, this region is thought to be involved in crossover events with the distal end of the short arm of the Y chromosome (de la Chapelle 1981;Polani 1982;Burgoyne 1982). The hypothesis that the distal ends of the short arms of X and Y are homologous on the molecular level has recently received additional experimental support (Goodfellow and Tippett 1981;Goodfellow et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This segment is of considerable interest because in this region, a reduction of X inactivation has been observed (Mohandas et al 1979;Miiller et al 1980;Migeon et al 1982). Furthermore, this region is thought to be involved in crossover events with the distal end of the short arm of the Y chromosome (de la Chapelle 1981;Polani 1982;Burgoyne 1982). The hypothesis that the distal ends of the short arms of X and Y are homologous on the molecular level has recently received additional experimental support (Goodfellow and Tippett 1981;Goodfellow et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In analogy to meiotic pairing of autosomes, these observations suggest a homology also on the level of DNA. Such a homology is supported by speculations (Haldane 1936;de la Chapelle et al 1981;Polani 1982;Burgoyne 1982) that cross-over does occur between homologous segments of X and Y.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Characterization and chromosomal localization of repetitive and unique sequences located on the Y. It may be assumed (5,10,31,(33)(34)(35) that, for a consider- It has been speculated (5,191 that the Y chromosome may contain a number of genes in addition to those associated with primary sexual development (probably located in the distal part of its short arm (5)). According to these ideas, these genes might take part in crossing over events with homologous X chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was (and is) assumed that the mammalian X and Y arose from an ancestral pair of homologues, they concluded that there is a region of homology between the X and Y in all mammalian species and that this region regularly synapses and crosses over during meiosis in a manner analogous to the autosomes. This assumption is still widely accepted (BURGOYNE 1982;POLANI 1982). Indeed, the idea has gained recent momentum from the molecular data for regular exchange of DNA between the X and Y in humans (ROUYER et al 1986).…”
mentioning
confidence: 99%